GUMPERZ'S CONTEXTUALIZATION CUES : A MEANS FOR INTERPRETING DISCOURSE IN CROSS-CULTURAL COMMUNICATION - Triastuti, Anita (Diksi, 2015)
<img src="data:image/png;base64,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